Data Driven Sigmoid Proportional-Integral-Derivative (SPID) Controller for Twin Rotor MIMO System - Goh, Ming Qian; Mohd Riduwan, Ghazali; Mohd Ashraf, Ahmad; Muhamad Shahir, Mohd Shukri (IETA, 2023)
This paper presents a data driven Sigmoid Proportional-Integral-Derivation (SPID) controller for a Twin Rotor Multiple-Input-Multiple-Output (MIMO) System (TRMS). A time-varying PID parameters based on sigmoid function is adopted to solve the low control accuracy of the conventional PID controller. In particular, the parameters of new version controller were vigorously changed based on its error signal of sigmoid function where its variability is limited in a predefined upper and lower bound. These SPID parameters are then optimized by using Adaptive Safe Experimentation Dynamics (ASED) method such that the control performance accuracy in terms of trajectory tracking error and control input energy are minimized. The simulations of step response analysis and stability analysis are conducted to evaluate the effectiveness of the proposed SPID controller compared to PID controller on TRMS system. Consequently, the results obtained from the simulations revealed that the SPID controller has successfully produced improvement in terms of objective function,